Waste from coconut plantation-coconut husk for making biodegradable composite / Roslee Mohamad Rais … [et al.] - Mohamad Rais, Roslee; Muhammed, Suhaimi; Munjat, Azli; Amasrek, Muhammed Hishamuddin; Mohamad, Mohd Akmal Zamir (Research Innovation Business Unit, 2014)
Waste from coconut plantation such as coconut husk can be effectively utilized for the making of biodegradable composite material. The effect of fiber content varying from 10% (by weight) to 30% on the strength properties and physical properties of the coconut husk-poly lactic acid (PLA) composite was investigated. The effect of alkali treatment on the properties such as tensile and flexural modulus was also studied. Results indicated that the best strength properties were achieved at 20% coconut husk fiber content. Both tensile and flexural modulus of the composite increased with increasing fiber content. Compared to treated coconut husk fiber, untreated composite exhibited high value of 3.5MPa for FMOR, 14998.76 N/mm for FMOE, 2075.13 N/mm for TMOE and 23.64 MPa for TMOR when 20% coconut husk fiber content was used. Meanwhile treated composite showed much higher values for the physical properties. Water absorption increased as the coconut husk fiber content increased.